Reception problem of Apostolic exhortation Amoris leatitia in terms of admission to sacraments penance and holy communion divorced persons - Janczewski, Zbigniew (Prawo Kanoniczne, 2018)
In the year 2015 pope Francis issued Apostolic exhortation Amoris laetitia. This document raises among other things the problem admission to sacraments penance and holy communion divorced persons. The first part of this article concerns scientific discussion about sacraments for divorced persons before 2014 year. Next part is about receiving the Body of the Lord according to the Familiaris consortio i Amoris laetitia. On the third part are canonists and theologian interpretations of the popes Francis exhortation. Last part of article is about application of this document to local conditions in the word.